Intracranial sewing needle in a man with seziure: A case of child abuse? - EKİNCİ, GAZANFER; İNANICI, MEHMET AKİF (ELSEVIER IRELAND LTD, 2007)
Physical abuse in infancy can cause persistent neurological deficits. Although intracranial foreign bodies are generally secondary to penetrating trauma or surgical procedures, rarely they also occur as a result of child abuse. A 32-year-old man presented with the complaint of generalized tonic clonic seizures to the Neurology Department of Marmara, University Hospital. Computerized tomography (CT) scan revealed a sewing needle located within the temporal lobe. The location and the position of the needle suggested that it must have been introduced in infancy through the lamdoid suture before the closure of it, as an unsuccessful deliberate homicide attempt or accidental injury. (C) 2006 Elsevier Ireland Ltd. All rights reserved.
Keywords: sewing needle; brain; foreign body; homicide; child abuse; NONACCIDENTAL INJURY; FRACTURES; BRAIN